Research on The Interaction Mechanism and Stability Analysis of Unsaturated Soil Slope and Support Structure - YuPin, Song; Ying, Feng (European Journal of Computational Mechanics, 2024)
Unsaturated soil, as a widely existing soil in nature, has significant differences in mechanical properties compared to saturated soil. Especially when considering water migration and changes, its stability issues become more complex. Therefore, in-depth research on the interaction mechanism and stability of unsaturated soil slopes and support structures is significant. This study first analyzes the mechanical properties of unsaturated soil and the influence of water migration on soil strength based on the principles of unsaturated soil mechanics. It establishes a mechanical model for unsaturated soil slopes. Subsequently, the pseudo-dynamic method was used to simulate the response of slopes under dynamic loads such as earthquakes and rainfall, and the deformation and failure modes of unsaturated soil slopes were explored. Regarding support structures, this article studies the interaction mechanism between retaining walls, anchor rods, and unsaturated soil slopes. A mechanical model of the interaction between the support structure and unsaturated soil slopes was established by analyzing the influence of the support structure on the distribution of soil pressure on the slope, as well as the stability and bearing capacity of the support structure itself. In terms of stability analysis, this article uses numerical analysis methods such as the limit equilibrium and finite element methods to evaluate the overall stability of unsaturated soil slopes and support structures. Suggestions for optimizing the design of support structures were proposed by comparing the stability performance of slopes under different support schemes. The experiment shows that increasing soil cohesion by 1kPa per unit area can increase the stability coefficient by about 5%. The interface friction angle between the fill and the wall back increases by 1 degree, resulting in an increase of approximately 7% in the overturning stability coefficient.